Financial Market Integration and Exchange Rate Policy - Rojas-Suarez, Liliana (IMF Working Papers; Working Paper ;, 1990)
This paper examines how a country's exchange rate policy should be adjusted when the degree of integration between domestic and external financial markets increases as a result of both domestic financial liberalization and the relaxation of capital controls. As the financial structure is opened and liberalized, the optimal scale of exchange market intervention changes as the relative importance of different domestic and foreign shocks for output and price stability is altered. Nonetheless, the response of the optimal degree of intervention to increases in the variances of the various domestic and foreign shocks is similar across all financial structures.